Experimental Investigation of High-power R744 Compressor Efficiencies at Varied Revolutions - Han Yi; Wu Jingyi; Hafner Armin (Zhileng xuebao, 2017)
The performance of a new 100-kW single-stage R744 piston compressor developed by Norwegian University of Science and Technology and Sintef is investigated in this paper. The oil circulation, volumetric efficiency, and overall efficiency are tested as an overview of the compressor performance. Experimental results with a pressure-ratio range from 1.9 to 4 under compressor revolutions of 1000 to 2500 r/min are reported. The results show that the highest oil circulation rate is 2.84%, acquired with a pressure ratio of 2.1 and a revolution of 2500 r/min, while the volumetric efficiency reaches a maximum value of 85.8% as a pressure ratio of 1.88 and revolution of 1000 r/min are reached. Optimum overall efficiencies of this compressor can be achieved in a pressure-ratio range from 1.5 to 2.5 and a compressor revolution near 1500 r/min. Specifically, the maximum value is obtained up to 79.1% with a revolution of 1500 r/min and a pressure ratio of 2.0. The fitted overall efficiency results are compared with the efficiency data from two commensurate products in a catalog. This illustrates that the overall efficiency of the new compressor is about 11.5% higher than the others when the pressure ratio ranges from 1.5 to 3.2.